Assignment of Rfp-Y to the chicken major histocompatibility complex/NOR microchromosome and evidence for high-frequency recombination associated with the nucleolar organizer region. - Miller, M M (1996)
Rfp-Y is a second region in the genome of the chicken containing major histocompatibility complex (MHC) class I and II genes. Haplotypes of Rfp-Y assort independently from haplotypes of the B system, a region known to function as a MHC and to be located on chromosome 16 (a microchromosome) with the single nucleolar organizer region (NOR) in the chicken genome. Linkage mapping with reference populations failed to reveal the location of Rfp-Y, leaving Rfp-Y unlinked in a map containing >400 markers. A possible location of Rfp-Y became apparent in studies of chickens trisomic for chromosome 16 when it was noted that the intensity of restriction fragments associated with Rfp-Y increased with increasing copy number of chromosome 16. Further evidence that Rfp-Y might be located on chromosome 16 was obtained when individuals trisomic for chromosome 16 were found to transmit three Rfp-Y haplotypes. Finally, mapping of cosmid cluster III of the molecular map of chicken MHC genes (containing a MHC class II gene and two rRNA genes) to Rfp-Y validated the assignment of Rfp-Y to the MHC/NOR microchromosome. A genetic map can now be drawn for a portion of chicken chromosome 16 with Rfp-Y, encompassing two MHC class I and three MHC class II genes, separated from the B system by a region containing the NOR and exhibiting highly frequent recombination.